The influence of international dispersed vs. home-based R&D on innovation performance - Bettina Peters; Anja Schmiele (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Recent years have shown a surge of firms globalising their innovation activities in order to gain from international knowledge. This paper evaluates this strategy by investigating whether firms with international R&D are more innovative than firms doing R&D only in their home country. One main novelty is that we shed light on two competing hypotheses whether stronger dispersed international R&D activities hamper or stimulate innovation. Second, we employ two well-established market-based indicators for innovation (introduction of and sales growth rates due to new products) instead of looking at inventions (patents). Using German CIS data for about 2100 firms, the econometric results show that firms with international R&D are more likely to launch new products (firm and market novelties) than firms with home-based R&D only. They are also more successful in terms of higher sales growth with firm novelties. However, given the introduction of a market novelty, the location of R&D doesn't matter for the sales growth with market novelties. The results concerning the degree of R&D internationalisation are mixed: The likelihood of introducing firm novelties increases with a stronger dispersion of foreign R&D activities (for market novelties only up to a specific point). The relationship between degree of R&D internationalisation and innovation success turns out to be inverse u-shaped.
Keywords: O32; F23; 330; R&D; Internationalisation; Innovation performance; Decentralisation; Innovation; Produktinnovation; Industrielle Forschung; Globalisierung; Betriebliche Forschung; Dezentrale Organisation; Schätzung; Deutschland